THE INFLUENCE OF UNDERSTANDING OF ACADEMIC RULES ON THE STUDENTS CONFLICT - Muhajir, Muhajir; Rismawati, Rismawati; Latief, Abdul (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2021)
This research about of understanding of academic rules which aimed to the describe the understanding the students of Muhammadiyah University of Makassar toward academic rules and to describe the influence of the students' understanding of academic rules and the occurrence of conflict between students in Muhammadiyah University of Makassar. This research is ex-post facto research, also known as a retrospective study because this research is a research of returning to an event or an event and then tracing back to know the factors that can cause the incident. Based on data analysis, it can be concluded that (1) students understanding of academic rules and perceptions about the conflict with the occurrence of conflict between students at the Muhammadiyah University of Makassar are in the medium category, (2) There is a positive influence on the students' understanding of academic rules with the occurrence of conflict between students at the Muhammadiyah University of Makassar